Isolation and identification of some plant growth promoting substances in compost and co-compost - Miezah, K.; Ofosu-Anim, J.; Budu, G.K.O.; Enu-Kwesi, L.; Cofie, Olufunke O. (Science Alert, 2008)
In this study, plant growth hormones in compost or co-compost prepared from human excreta and/or municipal solid waste were extracted and identified. Water (deionized) or 80% methanol (chilled) extracts were prepared from the composts for the isolation and identification of plant growth substances. The methanolic extracts of plant growth hormones fraction was further partitioned into cytokinin (fraction) using ethyl acetate and n-butanol; auxins (fraction) using diethyl ether and gibberellins (fraction) using sodium hydrogen carbonate and n-butanol. Five different concentrations of standard plant growth hormones; Benzyl Amino Purine (BAP), Gibberellic Acid (GA3) and Indole-3-Acetic Acid (IAA) were prepared and used in a bioassay test to compare the effects and concentration of the extracted plant growth hormones from the compost and co-compost. The presence of some plant growth hormones in the extracted samples from compost or co-compost was confirmed using the relative fluidity, (Rf) values of the co-chromatography using a standard hormone and the extracted plant growth hormones. The results indicated the presence of plant growth substances such as IAA, GA3 and cytokinins. In co-compost, the concentration of hormone were found to be 68.3 to 345.1 mg kg-1, 61.9 to 185.8 mg kg-1 and 250.4 to 312.7 mg kg-1 for auxins, cytokinins and gibberellins, respectively. Whereas in compost 42.0 to 248.8 mg kg-1, 33.1 to 198.3 mg kg-1 and 10.1 to 200.2 mg kg-1 of auxins, cytokinins and gibberellins, respectively were found.